Eating habits, nutritional status, and lifestyle correlates of body composition in Chinese university students: a cross-sectional study - Liu, Ling; Gong, Wan; Li, Jun; Zhou, Wei; Lin, Li (Frontiers in Public Health, 2025)
BackgroundUnhealthy eating habits and nutritional imbalances are prevalent among university students and may contribute to hidden obesity and metabolic risk. Understanding the dietary patterns and lifestyle factors associated with body composition is essential for designing effective interventions in this population.ObjectiveThis study aimed to assess the dietary habits, nutritional status, and lifestyle correlates of body composition among Chinese university students, with a focus on the prevalence of hidden obesity and low protein mass.MethodsA cross-sectional survey was conducted among 993 undergraduate students at a major Chinese university. Dietary intake, physical activity, sleep, and other lifestyle factors were assessed using validated questionnaires. Body composition, including body fat percentage and protein status, was measured with a bioelectrical impedance analyzer. Associations between dietary/lifestyle factors and body composition were examined using multivariable regression analyses.ResultsFewer than half of participants reported daily consumption of vegetables, and only 18.2% consumed fruit daily. Hidden obesity, defined as excessive body fat despite normal body mass index, was observed in 17.0% of students, significantly higher among females (23.0%) than males (1.1%) (p < 0.05). Low protein mass, as measured by bioelectrical impedance analysis, was present in 31.0% of students and was more prevalent among females (33.5%) than males (24.6%) (p < 0.05). Weekly fruit intake showed a weak but positive association with both body fat and protein percentages, after adjusting for confounders (p < 0.05).ConclusionUnbalanced dietary patterns, hidden obesity, and low protein mass are widespread among Chinese university students, with sex-specific differences. The relationship between fruit intake and body composition may reflect broader dietary or lifestyle behaviors rather than a direct protective effect.